Editorial on the "Special Issue in Honor of Dr. Michael Weber's 70th Birthday: Photodynamic Therapy: Rising Star in Pharmaceutical Applications" - Eduard Preis; Matthias Wojcik; Gerhard Litscher; Udo Bakowsky (MDPI AG, 2022)
Thousands of years ago, phototherapy or heliotherapy was performed by ancient Egyptians, Greeks, and Romans [...]